Multimodality, systemic functional-multimodal discourse analysis and production of videos in mathematics education - Borba, Marcelo C.; O'Halloran, Kay L.; Neves, Liliane Xavier (Springer Nature, 2022)
Dynamic media such as videos stand out as technologies that stimulate the senses in the production of mathematical knowledge, leading to new ways of knowing. Since the analysis of videos produced by students is a relatively new area in mathematics education, we will discuss some research on the field, but we will focus on one case study in order to illustrate how the approach can contribute to teaching and learning mathematics. In this context, we will discuss the results of research that investigates how the combination of semiotic resources to express mathematical ideas in digital videos can enhance mathematical understanding. The starting point of the discussion is the results of a survey in which students of the Distance Education Mathematics undergraduate course of Brazil produced videos to express mathematical concepts and ideas. The applied methodology was qualitative in nature, and virtual participant observation was adopted to follow the video production process in forums that took place in the virtual learning environment for the course. Systemic functional multimodal discourse analysis was adopted as a theoretical approach for analyzing the combinations of semiotic resources in the videos produced by the students. Detailed analysis of two of the videos produced by the research participants is presented in this chapter. The multimodal analysis of the videos shows that the multimodal nature of video made it possible for students to combine semiotic resources from traditional written forms of mathematical discourse (i.e., language, images, and mathematical symbolism) and audio-visual resources to create dynamic representations of mathematical content, resulting in expanded knowledge and understanding of key concepts and mathematical ideas.
Keywords: Digital technologies; Distance education; Mathematical videos; Multimodal analysis; Semantic expansion